387 Plastic Surgery Workload During The COVID-19 Pandemic. (4th May 2021) - Gohil, K; Al-Himdani, S; Walkden, A; Price, G
Abstract: Introduction: COVID-19 has been a formidable opponent to every aspect of the NHS. A comparative study examined referral workload at a regional Plastic Surgery Unit, Major Trauma Centre & Burns Facility during the initial stages of the lockdown period. Lessons learnt can then help prepare for the future. Method: From initial lockdown (24/03/2020), all Plastic Surgery referrals were documented for 28 days. This data was compared to the same period in 2019. Demographics, diagnosis, mechanism of injury and time to presentation and surgery were noted. Results: A total of 525 patients were managed, with a 48% reduction in referrals during lockdown. Hand trauma referrals reduced by 16% but increases in deliberate self-harm (100%), DIY injury (75%), lower limb trauma (250%) and burns (64%) were seen. Fewer work and school related injuries were managed in keeping with lockdown rules. Notably, access to surgical management did not alter. Conclusions: The COVID-19 pandemic significantly affected the workload of our service. Social behaviours and psychological impact were common contributing factors. As Plastic Surgeons this should be acknowledged and consideration of optimising mental health services and health education should be prioritised for the future.